2015
DOI: 10.1111/php.12528
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dermal Brimonidine Applications Against UV Radiation‐induced Skin Tumors, Epidermal Hyperplasia and Cell Proliferation in the Skin of Hairless Mice

Abstract: Brimonidine at 0.18%, 1% and 2% concentrations applied topically in hairless mice significantly decreased tumor burden and incidences of erythema, flaking, wrinkling and skin thickening induced by UVR. The unbiased median week to tumor ≥1 mm was increased by the 1% and 2% concentrations. The tumor yield was reduced by all concentrations at week 40 for all tumor sizes but the ≥4 mm tumors with the 0.18% concentration. At week 52, the tumor yield was reduced for all tumor sizes and all brimonidine concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Therefore, the delay in SCC development observed in the mice administered 1% topical brimonidine cream before UVR exposure was most likely caused by a UVR absorption by the drug. Brimonidine can absorb light in the UVB wavelength range (280-315 nm), as shown by Bouvier et al (12). However, there can be multiple reasons for a delay in photocarcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Therefore, the delay in SCC development observed in the mice administered 1% topical brimonidine cream before UVR exposure was most likely caused by a UVR absorption by the drug. Brimonidine can absorb light in the UVB wavelength range (280-315 nm), as shown by Bouvier et al (12). However, there can be multiple reasons for a delay in photocarcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…However, we have previously investigated the same vehicle used in groups 1, 3 and 5 and it did not alter the time to tumor development or induce erythema in the same strain of mice. However, Bouvier et al (12) demonstrated that the commercial gel-formulation vehicle alone did not influence the carcinogenic response compared to UVR treatment in the absence of gel. Other studies, such as that by Fowler et al (6), evaluated the optimal concentration, efficacy and safety of brimonidine gel for treating erythema in patients with rosacea and showed that the vehicle formulation did not aggravate erythema or other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical 2% of brimonidine applied 1 h before or just after UVB irradiation on hairless mice has shown protective effect against UV radiation-induced skin tumours, epidermal hyperplasia and cell proliferation, partly making an interesting use in patients with lupus and dermatomyositis. 7 We have been using topical brimonidine in other patients with heliotrope rash, but it has not always worked due to patient's intolerance or lack of efficacy.…”
Section: Letters To the Editormentioning
confidence: 99%